Analisis Pendapatan dan Nilai Tambah Agroindustri Keripik Ayam di Desa Kesiman Petilan, Denpasar Timur - WIDIANTARI, PUTU DEWI; ANTARA, MADE; DJELANTIK, A.A.A. WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022, 2022)
Analysys of Income and Added-Value of Chicken Chips Agroindustry in Kesiman Petilan Village, East Denpasar.  Covid-19 Pandemic has many impacts on all business actors, either large-scale, small-scale, or medium-scale. The business actors of chicken chips agroindustry are also impacted by the pandemic in terms of production processes and income. This study aims to: (1) Analyze the income of the business actors involved in the chicken chips agroindustry in Kesiman Petilan Village, East Denpasar, (2) Analyze the added-value of the chicken chips products in the agroindustry in Kesiman Petilan Village, East Denpasar, and (3) Identify the problems that have been experienced by the business actors in the chicken chips agroindustry during Covid-19 Pandemic. The analysis technique used was income analysis, added-value analysis, and qualitative descriptive. The results of the study show that: (1) The amount of income in chicken chips agroindustry in Kesiman Petilan Village before Pandemic was IDR 2,785,853.90 while during the Pandemic was IDR 2,066,123.90, (2) The added-value of chicken chips before Pandemic was IDR 10,369.40 while during the Pandemic was IDR 10,114.85, and (3) The agroindustry have faced several problems, including the difficulties to obtain raw materials, the increase of raw materials prices, declining sales, and marketing.